Relapse of neuromyelitis optica with occipital neuralgia and elevated CSF neopterin. Issue 4 (25th April 2020) - Miyaue, Noriyuki; Yabe, Hayato; Yamanishi, Yuki; Tada, Satoshi; Ando, Rina; Nagai, Masahiro
Abstract: A 64‐year‐old woman with anti‐aquaporin‐4 antibody‐positive neuromyelitis optica presented with pain and dysesthesia in the left occipital region. Cervical magnetic resonance imaging showed a new high‐intensity area on the left side of the spine (C1‐C2 level), close to a pre‐existing lesion. Cerebrospinal fluid analysis revealed elevated neopterin (53.1 nmol/L) without pleocytosis. The neopterin level normalized 2 weeks (22.0 nmol/L) and 2 months (18.9 nmol/L) after intensified steroid therapy. Occipital neuralgia should be considered a common clinical feature of neuromyelitis optica, and cerebrospinal fluid neopterin may be a useful, sensitive biomarker for central nervous system inflammation in these patients.